DESIGN OF ANTI-IMPАСТ MICRO-ACCELERATION SENSOR IMITATING SHRIMP CLAW - ZHANG Xu; ZHAO Rui; SHI YunBo; ZU KaiXuan; ZHANG JieYu; YAN XiaoPeng (Jixie qiangdu)
Aiming at the damage of a Iow-range micro-electro-mechanical system(MEMS) acceleration sensor under tens of thousands of gn overload during the measurement of outer ballistic information of conventional weapons and ammunition, a kind of shrimp claw anti-impact micro-acceleration sensor was proposed, which could realize the index requirements of anti-overload 30 000gn and range 50gn. The finite element simulation results show that the displacement of the sensor is 0. 99 μm and the sensitivity is 0.124 pF/gn under 50gn load. The maximum equivalent stress of the acceleration sensor under 30 000gn overload is reduced from 1 022.5 MPa to 84.326 MPa, which effectively improved the reliability of the sensor.